Three‐Dimensional Scaffolds of Carbonized Polyacrylonitrile for Bone Tissue Regeneration1. (7th July 2014) - Ryu, Seungmi; Lee, Choonghyeon; Park, Jooyeon; Lee, Jun Seop; Kang, Seokyung; Seo, Young Deok; Jang, Jyongsik; Kim, Byung‐Soo
Abstract Carbon‐based materials have been extensively studied for stem cell culture. However, difficulties associated with engineering pure carbon materials into 3D scaffolds have hampered applications in tissue engineering and regenerative medicine. Carbonized polyacrylonitrile (cPAN) could be a promising alternative, as cPAN is a highly ordered carbon isomorph that resembles the graphitic structure and can be easily processed into 3D scaffolds. Despite the notable features of cPAN, application of cPAN in tissue engineering and regenerative medicine have not been explored. This study, for the first time, demonstrates the fabrication of microporous 3D scaffolds of cPAN and excellent osteoinductivity of cPAN, suggesting utility of 3D cPAN scaffolds as synthetic bone graft materials. The combination of excellent processability and unique bioactive properties of cPAN may lead to future applications in orthopedic regenerative medicine.